Effects of cysteamine and antibody to somatostatin on islet cell function in vitro. Evidence that intracellular somatostatin deficiency augments insulin and glucagon secretion. - Patel, Y C (1985)
In this study we have characterized the effects of cysteamine (CHS) on the cellular content and release of immunoreactive somatostatin (S-14 LI), insulin (IRI), and glucagon (IRG) from monolayer cultures of neonatal rat islets. Incubation of cultures with 0.1-10 mM CHS for 1 h led to an apparent, dose-dependent reduction of cellular S-14 LI that was 50% of control at 0.3 mM, 87% at 1 mM, and 95% at 10 mM. IRI content was unaffected by CHS up to 1 mM, but at 10 mM 90% loss of IRI occurred. All concentrations were without effect on IRG content. The loss of S-14 LI and IRI was completely reversible with time, but with different recovery rates for the two hormones (48 h for S-14 LI, and 72 h for IRI). Released S-14 LI rose progressively with increasing doses of CHS from 21 +/- 2.5 pg/ml per hour to 41 +/- 1.4 pg/ml per hour at CHS concentrations of 5 mM and 10 mM. IRI and IRG secretion were both also significantly enhanced (by 55% and 88%, respectively), despite the elevated medium S-14 LI. Since CHS reduced cellular S-14 LI but augmented medium S-14 LI, the relative effects of CHS (1 mM) and immunoneutralization with antibody to S-14 LI on IRI and IRG secretion were tested. Anti S-14 LI alone stimulated basal IRG (67%) but not IRI. Cultures rendered S-14 LI deficient with both CHS and anti-S-14 LI exhibited threefold and 2.3-fold potentiation of IRG and IRI secretions, respectively, greater than that expected from the separate effects of the two agents. Increasing medium glucose from 2.8 mM to 16.7 mM stimulated IRI release by 86% and suppressed IRG by 53%. CHS (1 mM) and anti-S-14 LI further augmented stimulated IRI release, by 30%; although 16.7 mM glucose suppression of IRG was still maintained under these conditions, the quantitative IRG response was significantly greater. These results suggest that CHS induces an apparent loss of islet S-14 LI, and at high doses, of IRI as well, but has no effect on A cells. Complete islet S-14 LI deficiency augments IRI and IRG secretion over a wide range of glucose concentrations, suggesting a physiological role of D cells on B cell and A cell regulation. D cell modulation of B cells requires cellular but not extracellular S-14 LI, being mediated probably though direct intracellular communication, whereas the A cells seem to be regulated by both direct contact as well as through locally secreted S-14 LI.